Analisis Efektivitas Penertiban Penyandang Masalah Kesejahteraan Sosial Di Dinas Sosial Provinsi DKI Jakarta - Jauhar Rosyidi; Dedy Kusna Utama (Jurnal Ilmu Administrasi Publik, 2021)
The purpose of this study was to analyze the effectiveness of controlling people with social welfare problems (PMKS) by the DKI Jakarta Provincial Social Service. The research method used in this research was descriptive  qualitative  method,  with  data  collection techniques  in  the  form of questionnaire distribution and literature study. The research questions posed are: what is the analysis of the effectiveness of controlling PMKS by the DKI Jakarta Provincial Social Service; what factors are the obstacles to effectiveness; and what efforts need to be made by the service leaders to overcome these obstacles. The results of the study prove that the effectiveness of controlling people with social welfare problems by the DKI Jakarta Provincial Social Service is good. From the results of interviews, it can be concluded that additional employees are needed. The inhibiting factors for effectiveness are the low number of certified employees and the quantity of human resources that have not met the required number. The suggestion put forward by the researcher is that the DKI Jakarta Provincial Social Service increase the commitment of officers in handling PMKS, improve  the  supporting  facilities  and  infrastructure  for  the  control,  and increases the number of employees or personnel so that the department is able to work wel.